(untitled) (International Journal of Innovative Technologies in Economy, 2022)
The article discusses the role of copywriting in social media, both at the Georgian and international levels. After the spread of the COVID-19 pandemic, the attention of almost all countries of the world, including Georgia, was focused on using social media and especially copywriting for business development. The objective of the study is to study the problems of Highlighting the role of copywriting for successful business operations and to develop recommendations for its active use. The methods of material collection and analysis were used in the development of the paper. The method of data collection is mainly used in worldwide statistical data regarding the use of social media, on the basis of which the possibilities of using copywriting in successful business management were identified, the ways of their implementation were analyzed and outlined. In Georgia, as well as in other countries of the world, where the level of use of copywriting in business is less, it is important to raise the awareness of copywriting; To provide the public with correct and reliable information not only about the essence of copywriting, also about the need for its use in business. In Georgia for use copywriting in business, it is necessary to: Business representatives to share the experience of developed countries through social media and copywriting in terms of business; To create training-practical courses, which will teach the interested person not only the theoretical material about copywriting, but also it is practical application, this is important for training a qualified copywriter; To subsidize the free study of such courses, which ensure the formation of qualified copywriters, by means of sharing the experience of foreign specialists.